PENERAPAN HUKUM QANUN ACEH NOMOR 6 TAHUN 2014 TENTANG HUKUM JINAYAT TERKAIT TINDAK PIDANA (JARIMAH) KHALWAT - Muhammad Yunus Bidin (Prodi Ilmu Hukum, Universitas Teuku Umar, 2019)
Law Number 44 of 1999 concerning the Privileges of Aceh is a juridical basis for the implementation of the Islamic Sharia in a comprehensive, besides organizing customary life, organizing education and the role of ulama in the determination of regional policies. In connection with this the Aceh Government has issued several derivative legal products in the form of qanun as implementing technical regulations, namely: First, Aceh qanun Number 11 of 2003 concerning the Implementation of Islamic Sharia in the Field of Aqeedah, Worship, and Islamic Sharia; Second, Aceh qanun Number 12 of 2003 concerning Khamar; Third, Aceh qanun Number 13 of 2003 concerning Maysir or Gambling; Fourth, Aceh Qanun Number 14 of 2014 concerning Seclusion as amended in Aceh Qanun Number 6 of 2014 concerning criminal Law. This is an unusual breakthrough in the conception of positive law, which then has implications for its application to achieve expectations in the future, as a prosperous and Islamic society.Keywords: Aceh, Qanun, Law.